2014
DOI: 10.1002/jcc.23711
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of small molecules on helical gold nanorods: A relativistic density functional study

Abstract: We study the adsorption of a variety of small molecules on helical gold nanorods using relativistic density functional theory. We focus on Au40 which consists of a central linear strand of five gold atoms with seven helical strands of five gold atoms on a coaxial tube. All molecules preferentially adsorb at a single low-coordinated gold atom on the coaxial tube at an end of Au40. In most cases, there is significant charge transfer (CT) between Au40 and the adsorbate, for CO and NO2, there is CT from the Au40 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Adsorption of O 2 onto small, unsupported Au n q (with n = 1–55 and q = −1,0,1) clusters has been extensively studied using DFT. ,, Although the adsorption strength as well as the geometry depend on the calculation details, such as the employed exchange-correlation functional, several trends can be extracted.…”
Section: Effect Of the Surface Geometry On O2 Dissociationmentioning
confidence: 99%
“…Adsorption of O 2 onto small, unsupported Au n q (with n = 1–55 and q = −1,0,1) clusters has been extensively studied using DFT. ,, Although the adsorption strength as well as the geometry depend on the calculation details, such as the employed exchange-correlation functional, several trends can be extracted.…”
Section: Effect Of the Surface Geometry On O2 Dissociationmentioning
confidence: 99%
“…In our DFT calculations, the exchange-correlation functional within the generalized gradient approximation (GGA) was employed. Specifically, we use the Becke exchange functional with the Perdew correlation functional (BP86) that was used in our previous studies. , We note that some GGA exchange-correlation functionals, and B3LYP in particular, can be problematic for gold clusters because they tend to favor planar geometries and electron affinities are not well reproduced . However, recent results for neutral gold clusters have shown that the BP86 functional gives excellent results for geometries and adsorption energies, and is sufficiently accurate for the neutral gold clusters we consider in this study .…”
Section: Computational Methodsmentioning
confidence: 99%
“…However, recent results for neutral gold clusters have shown that the BP86 functional gives excellent results for geometries and adsorption energies, and is sufficiently accurate for the neutral gold clusters we consider in this study . As in our previous studies, , we use the Los Alamos small-core pseudopotential of Hay and Wadt together with the corresponding double-ζ basis set. It is well established that small-core pseudopotentials of this sort can accurately describe relativistic and electron correlation effects in atoms and molecules. , In addition, vibrational frequencies, infrared spectra, and VCD spectra for the optimized structures are calculated.…”
Section: Computational Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a density functional theory (DFT) study, we showed that segments of the (7, 3) single-walled nanotube with a central linear strand, Au 24 , Au 32 , and Au 40 , are stable as free-standing structures and represent atomic cluster analogues of the helical gold wires . That is, they are local minima on the potential energy surface which are robust in the sense that they remain stable when a variety of species are adsorbed on them. , However, they have undercoordinated gold atoms at their ends and, at room temperature, ab initio molecular dynamics calculations indicate that they transform to compact core–shell structures . In this study, we extend these nanorods to include Au 48 and Au 56 and focus on their optical properties.…”
Section: Introductionmentioning
confidence: 99%